ОСМИСЛЕННЯ ПОНЯТЬ «ГЕРОЙ», «ГЕРОЇЗМ» У ФІЛОСОФСЬКІЙ ДУМЦІ - Йовенко, Лариса (Збірник наукових праць Уманського державного педагогічного університету, 2020)
На основі аналізу філософської літератури досліджено сутність понять «герой», «героїзм», здійснено опис історії феномену героїзму, простежуються зв’язки означених явищ з поняттями «пасіонарність», «геніальність», «негероїчне», мотивами подвижництва та смерті, виокремлюються варіанти співіснування різних концепцій «героя», виявляються специфічні ознаки героїчного вчинку, встановлюються зв’язки героїчного зі словесним мистецтвом. В розвідці зосереджено увагу на філософській думці ХХ століття, оскільки в цей період відбулася активізація наукового пошуку уточнення означених понять. На основе анализа философской литературы исследована сущность понятий «герой», «героизм», осуществлено описание истории феномена героизма, прослеживаются связи указанных явлений с понятиями «пассионарность», «гениальность», «негероическое», мотивами подви-жничества и смерти, выделяются варианты сосуществования различных концепций «героя», выявляются специфические признаки героического поступка. В работе внимание сосредоточено на философской мысли ХХ века, поскольку в этот период произошла активизация научного поиска уточнения указанных понятий. In the article the one of the most important phenomenon that is in the circle of scientific interests of literature, art, ethics, aesthetics and history was discussed. The essence of concepts «hero», «heroism» based on the analysis of philosophical literature was explored. The description of the history of the phenomenon of heroism in different sources was made. The connection of aforementioned phenomena could be traced with such concepts as: «passionarity», «genius», «heroic way», the motives of selfless devotion and death, variants coexistence of different concepts of «hero» were distinguished, specific signs of heroic action were demonstrated. It reflected the socio-cultural settings of specific historical period and indicated the variability of ideas about the status of this phenomenon. It was defined that people constantly were coming back to that category and fixing with that fact the highest level of spiritual beauty and activity of personality, which was able to give hope and to lead, to provoke the desire to imitate.The attention in the research work was focused on the philosophical idea of the twentieth century because at that period there was intensification of scientific research for clarification of those concepts.